2015
DOI: 10.3390/s150202644
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Properties of Multiwalled Carbon Nanotubes Grown in MW Plasma Torch: Electronic and Electrochemical Behavior, Gas Sensing, Field Emission, IR Absorption

Abstract: Vertically aligned multi-walled carbon nanotubes (VA-MWCNTs) with an average diameter below 80 nm and a thickness of the uniform VA-MWCNT layer of about 16 μm were grown in microwave plasma torch and tested for selected functional properties. IR absorption important for a construction of bolometers was studied by Fourier transform infrared spectroscopy. Basic electrochemical characterization was performed by cyclic voltammetry. Comparing the obtained results with the standard or MWCNT‐modified screen-printed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…32 Thus, carbon based nanomaterials, being cheap and easily processable and with a high surface to volume ratio and tunable electrical properties, are advantageously applicable for use as resistive or capacitive chemical sensors. 17,33,34 Extensive research has been carried out on the synthesis and application of solid carbon spheres. However, the same cannot be said for their hollow carbon sphere (HCS) counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…32 Thus, carbon based nanomaterials, being cheap and easily processable and with a high surface to volume ratio and tunable electrical properties, are advantageously applicable for use as resistive or capacitive chemical sensors. 17,33,34 Extensive research has been carried out on the synthesis and application of solid carbon spheres. However, the same cannot be said for their hollow carbon sphere (HCS) counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that the low‐density network formed by MWCNT imparts the surface, radiation trapping characteristic similar to an ideal black body . Majzlíková et al demonstrated that vertically aligned MWCNTs show strong absorption in 2.5–25 µm range . Preparation of SWCNT‐based IR absorber coating with absorbance of 90% has been previously demonstrated .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it can be applied for optical and biomedical devices, as well as various sensors. In a recent work, vertically aligned multi-walled carbon nanotubes were prepared with a diameter of less than 80 nm and uniform thickness of 16 μm, by employing microwave plasma torch with a high-speed process of only 60–120 s [99]. Carbon-encapsulated magnetic materials were also obtained by plasma as described in the previous section [88].…”
Section: Application Of Plasma For the Synthesis And Modification mentioning
confidence: 99%